A Forward Genetic Screen Reveals that Calcium-dependent Protein Kinase 3 Regulates Egress in Toxoplasma - Garrison, Erin; Treeck, Moritz; Ehret, Emma; Butz, Heidi; Garbuz, Tamila; Oswald, Benji P.; Settles, Matt; Boothroyd, John; Arrizabalaga, Gustavo (PLoS pathogens, 2012)
Egress from the host cell is a crucial and highly regulated step in the biology of the obligate intracellular parasite, Toxoplasma gondii. Active egress depends on calcium fluxes and appears to be a crucial step in escaping the attack from the immune system and, potentially, in enabling the parasites to shuttle into appropriate cells for entry into the brain of the host. Previous genetic screens have yielded mutants defective in both ionophore-induced egress and ionophore-induced death. Using whole genome sequencing of one mutant and subsequent analysis of all mutants from these screens, we find that, remarkably, four independent mutants harbor a mis-sense mutation in the same gene, TgCDPK3, encoding a calcium-dependent protein kinase. All four mutations are predicted to alter key regions of TgCDPK3 and this is confirmed by biochemical studies of recombinant forms of each. By complementation we confirm a crucial role for TgCDPK3 in the rapid induction of parasite egress and we establish that TgCDPK3 is critical for formation of latent stages in the brains of mice. Genetic knockout of TgCDPK3 confirms a crucial role for this kinase in parasite egress and a non-essential role for it in the lytic cycle.